Spatial Characteristics of Recycled and Primordial Reservoirs in the Deep Mantle. (30th March 2021) - Jackson, M. G.; Becker, T. W.; Steinberger, B.
Abstract: The spatial distribution of the geochemical domains hosting recycled crust and primordial (high‐ 3 He/ 4 He) reservoirs, and how they are linked to mantle convection, are poorly understood. Two continent‐sized seismic anomalies located near the core‐mantle boundary—called the Large Low Shear Wave Velocity Provinces (LLSVPs)—are potential geochemical reservoir hosts. It has been suggested that high‐ 3 He/ 4 He hotspots are spatially confined to the LLSVPs, hotspots sampling recycled continental crust are associated with only one of the LLSVPs, and recycled continental crust shows no relationship with latitude. We reevaluate the links between LLSVPs and isotopic signatures of hotspot lavas using improved mantle flow models including plume conduit advection. While most hotspots with the highest‐ 3 He/ 4 He can indeed be traced to the LLSVP interiors, at least one high‐ 3 He/ 4 He hotspot, Yellowstone, is located outside of the LLSVPs. This suggests high‐ 3 He/ 4 He is not geographically confined to the LLSVPs. Instead, a positive correlation between hotspot buoyancy flux and maximum hotspot 3 He/ 4 He suggests that it is plume dynamics (i.e., buoyancy), not geography, which determines whether a dense, deep, and possibly widespread high‐ 3 He/ 4 He reservoir is entrained. We also show that plume‐fed EM hotspots (enriched mantle, with low‐ 143 Nd/ 144 Nd), signaling recycled continental crust, are spatially linked to both LLSVPs, and located primarily in the southern hemisphere. Lastly, we confirm that hotspots sampling HIMU ("high‐μ, " or high 238 U/ 204 Pb) domains are not spatially limited to the LLSVPs. These findings clarify and advance our understanding of deep mantle reservoir distributions, and we discuss how continental and oceanic crust subduction is consistent with the spatial decoupling of EM and HIMU. Key Points: High‐ 3 He/ 4 He signatures at hotspots are not confined to the Large Low Shear Wave Velocity Provinces (LLSVPs), because the high‐ 3 He/ 4 He Yellowstone hotspot is not linked to the LLSVPs Plume dynamics (i.e., buoyancy), not geography, determines whether a deep, dense, and possibly widespread high‐ 3 He/ 4 He domain is entrained Plume‐fed EM (enriched mantle) hotspots are associated with the southern regions of both LLSVPs; HIMU hotspots are not linked to the LLSVPs